The use of biological agents in pregnant women affected by autoimmune disorders: Why we need more research of this neglected area. (September 2021) - Carnovale, Carla; Parisi, Francesca; Battini, Vera; Zavatta, Alice; Cheli, Stefania; Cattaneo, Dario; Gringeri, Michele; Mosini, Giulia; Guarnieri, Greta; Cammarata, Gianluca; Cetin, Irene
Abstract: Women of childbearing age are largely affected by several autoimmune disorders (the estimates range between 1.5 and 10 per 10, 000). The increasing number of effective biological agents has dramatically revolutionized the treatment of these clinical conditions, ameliorating the patient's quality of life. The use of these agents by women during pregnancy is growing to ensure the disease activity control and avoid adverse health outcomes. However, for many newer biological agents, the degree of information concerning their use in pregnancy is often incomplete to perform a conclusive risk assessment on fetal and maternal health given the exclusion of this specific population from pharmacological clinical trials. More recently, the COVID-19 pandemic has confirmed the unacceptable inequities of pharmacological research and medical treatment for pregnant and lactating women, exacerbating the need for filling the gaps of quantitative and qualitative pharmacology data in this sensitive population. ere we summarize (i) what is already known about safety and effectiveness of biological agents in this understudied population (with specific focus on pregnancy-related health outcomes), and what we are going to learn from the on-going studies among pregnant women treated with biological agents; (ii) the methodological and ethical considerations that characterize the pharmacological research in pregnancy, also discussing emerging evidence on the use of therapeutic drug monitoring (TDM) in this clinical setting. Graphical Abstract: ga1